A bacterial toxin and a non-enveloped virus hijack ER-to-cytosol membrane translocation pathways to cause disease - He, Kaiyu (Crit Rev Biochem Mol Biol, 2015)
A dedicated network of cellular factors ensures that proteins translocated into the endoplasmic reticulum (ER) are folded correctly before they exit this compartment en route to other cellular destinations or for secretion. When proteins misfold, selective ER-resident enzymes and chaperones are recruited to rectify the protein-misfolding problem in order to maintain cellular proteostasis. However, when a protein becomes terminally misfolded, it is ejected into the cytosol and degraded by the proteasome via a pathway called ER-associated degradation (ERAD). Strikingly, toxins and viruses can hijack elements of the ERAD pathway to access the host cytosol and cause infection. This review focuses on emerging data illuminating the molecular mechanisms by which these toxic agents co-opt the ER-to-cytosol translocation process to cause disease.